Exploring the factors impacting physicians' attitudes toward health information exchange with patients in Jordanian hospitals - Emad Dahiyat; Faris El-Dahiyat; Ghaleb El Refae; Zaheer- (Taylor & Francis Group, 2023)
Abstract Background The uniqueness of the physician-patient relationship and the latter's lack of medical experience and knowledge necessitate providing patients with accurate and timely information necessary to engage them in treatment decision-making. Without detailed information from their physicians, patients cannot understand their medical condition, assess treatment options, and participate meaningfully in their care. Objectives The present research determines the main factors influencing physicians' attitudes toward health information exchange with patients in Jordanian hospitals. The fundamental question addressed by this paper is why Jordanian physicians are reluctant to provide their patients with detailed health information about the potential risks, complications, and benefits of proposed treatments and other recognised alternative therapies. Method This study is qualitative in nature, adopting face-to-face interviews as the key instrument of data collection in two hospitals in Jordan. The chief consideration of the sampling process was to select direct informants whose input would generate accurate results that might be generalised or translated to other contexts or settings. Thematic analysis was then used, and all participants' opinions, answers, and interactions were transcribed and then reduced into themes and patterns for research, as per similarities and relationships, through coding and representing the data. Key findings The findings show that most patients in government hospitals, especially those elderly, poorly educated, or inexperienced, choose practitioners based solely on medical service fees and costs rather than quality and convenience. On the other hand, the large number of patients attending public hospitals and the insufficiency of physicians' financial incentives in such hospitals may discourage physicians from providing patients with detailed health information. Matters, however, take a different turn in private hospitals, in which many physicians improve the patient experience to keep him and attract others by sharing information with patients about their health and treatment. However, it was noted that some physicians at such hospitals still rely heavily on their relations with health insurance companies to attract patients rather than on meaningful communication with their patients. Finally, the present findings reveal that the absence of a clear legal duty of medical disclosure negatively influences the amount of information received during the clinic visit. Conclusions The fact that the level of communication in Jordanian healthcare settings has not been determined in detail opens the door to unnecessary healthcare expenditure and creates uncertainty concerning the amount of information that patients need to know in order to be involved in their treatment decision-making. The lack of proper control and quality monitoring may also negatively affect the interests of patients and their rights to receive adequate information about their health status.